About the management of state scientific and technology programs - Long, Hoang Xuan (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
The management of state S&T programs (hereinafter referred to as S&T programs) have been attracting much attention. In this paper, management of state S&T programs is presented on the basis of a number of approaches such as: distinguish between units of state management, state management services and state management support;; distinguish between managing S&T programs and managing scientific projects; Comparison between the S&T programs management apparatus according to the general principle and the S&T management apparatus in our country at present. The objective of this research is to contribute to the renewal of S&T programs management in our country under the both cautious and positive mottoes. Code: 17090501